Developing a Career Monopoly Game to Enhance Career Planning among Senior High School Students - Kentrico Yendi; Rafael Lisinus Ginting (Insight: Journal of Counseling and Psychology, 2026)
Career planning is an essential developmental task for adolescents, particularly senior high school students who are approaching important educational and occupational transitions. However, many students continue to experience difficulties in identifying their interests, abilities, and future career goals, resulting in uncertainty regarding career decision-making. To address this issue, innovative and engaging career guidance media are needed to facilitate students’ career exploration and planning processes. This study aimed to develop and evaluate the feasibility of a Career Monopoly game as a guidance and counseling medium for enhancing career planning among senior high school students. This study employed a Research and Development (R&D) approach using the Four-D (4-D) model developed by Thiagarajan, Semmel, and Semmel, consisting of the stages of define, design, develop, and disseminate. The product was developed based on a needs analysis conducted among Grade XI students at SMAN 2 Medan. The feasibility of the developed media was evaluated through expert validation and practicality testing. The validation process involved two content experts and two media experts, while practicality testing was conducted with a school counselor and eight Grade XI students. Data were collected using validation and student response questionnaires and analyzed descriptively. The findings indicated that the Career Monopoly game achieved a content validity score of 92.5%, which falls within the very feasible category. The media was also positively evaluated in terms of visual design, interactivity, usability, and instructional quality. Furthermore, the practicality assessment revealed an overall student response score of 94%, indicating a very high level of practicality. Students perceived the game as attractive, easy to use, and helpful in understanding career-related information and developing career plans. The integration of career information and Holland’s RIASEC personality framework further supported students’ self-exploration and career decision-making processes. In conclusion, the Career Monopoly game is a valid and practical guidance and counseling medium for supporting career planning among senior high school students. The findings suggest that game-based career guidance media can enhance student engagement and provide meaningful learning experiences that facilitate career exploration and planning. Therefore, the Career Monopoly game may serve as an innovative alternative for delivering career guidance services in schools.